Meningkatkan E-Loyalitas (Model dan Kerangka Kerja Konseptual) - Yohanes Suhari (Dinamik, 2003)
This paper presents n conceptual model of Internet-based business-consumer relationship marketing with a focus on the context, content, and the process of relationship development from the consumer's perspective. The model con be divided into two broad groups. The first group is a set of contextual factors (environment, parties to the relationship, consumption task) that influence relationship development. The second group is the content and process of relationship development that can be viewed via three interrelated conceptual phases: consumer motives to seek interaction, exploration and interaction, and relationship bonding. With the rapid growth of E-commerce and on-line consumer shopping trends, the importance of building and maintaining customer loyalty in electronic marketplaces has come into sharper focus in marketing theory and practice. This paper also to present a conceptual framework of "e-loyalty" and its underlying drives.